Relative resistance of indigenous and exotic accessions of apple against woolly apple aphid (Eriosoma lanigerum) - NAGA, K C; SHARMA, R K; SUBRAMANIAN, S; VERMA, M K; PRAMANICK, K K; KUMAR, J (The Indian Journal of Agricultural Sciences, 2019)
Twelve apple accessions, belonging to six apple species were screened to ascertain the relative resistance against Woolly apple aphid (WAA), Eriosoma lanigerum (Hausmann). The experiment was conducted at ICARIndian Agricultural Research Institute Regional Station, Shimla, India (1900 m, 31°06’ 21.6’’N, 77°07’02.5’’E) during 2014–16. The screening was done by visual indexing technique of apple accessions based on mean infestation of WAA on a 0–4 rating scale. The mean infestation rating differed significantly among apple accessions and ranged from zero to 3.42. Three apple accessions were scored the lowest (zero) mean infestation rating, i.e. Northern spy, M. prunifolia var. Maruba Borkh. and M. prunifolia var. Ringo-Asami. The M. baccata (Kashmir) and M. pumila were scored the highest (3.42) mean infestation rating, a pair wise comparison using Kruskal-Wallis test shows a significantly higher mean infestation on apple accessions M. baccata (Dhak), M. baccata (Kashmir) and M. pumila compare to Northern spy, M. prunifolia var. Maruba and M. prunifolia var. ringo Asami.The present study gave an update of resistance screening of apple accessions against WAA by Kishore et al. (2006) and this data set may help in identifying resistance sources which may directly be used as rootstocks to combat the edaphic WAA problem in apple and the identified resistance sources could be utilized for developing improved apple accessions with durable resistance and improved quality traits of high yielding apple cultivars. Further studies are required to unravel the mechanism of resistance in resistant apple accessions against WAA.